CHRM3-Associated miRNAs May Play a Role in Bile Acid-Induced Proliferation of H508 Colon Cancer Cells - Çağdaş Aktan; Fatih Tekin; Nevin Oruç; Ömer Özütemiz (Turkish Journal of Gastroenterology, 2023)
Background: It was well defined that proliferative effects of bile acids on colon epithelium are through interaction with muscarinic-3 receptors. Recently, microRNA emerged as an important regulator of gene expression and has been implicated in pathogenesis of many malignancies. However, the interaction of CHRM3 and microRNAs and their potential effects on colon carcinogenesis remains to be elucidated. Methods: In the current study, analysis of cell proliferation for 6 days after treatment with sodium taurolithocholate was analyzed by using WST-1 method. microRNAs which possibly target CHRM3 were identified by in silico analyses. Expression profiling of these microRNAs, expression changes of CHRM3 gene at mRNA level for H508 and SNU-C4 colon cancer cells were analyzed by quantitative polymerase chain reaction; the protein level of CHRM3 was analyzed using Western blot; apoptotic experiments were analyzed using the Annexin V assay. The Gene Ontology and the Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses were performed using the miRPath v3.0. Results: It was found that the expression level of CHRM3 gene was 6.133 ± 0.698-fold in H508 cells compared with SNU-C4 cells (P =.004). Treatment of H508 cells with sodium taurolithocholate caused 1.34 ± 0.4156-fold change in the expression level of CHRM3 gene (P =.0448). No apoptotic changes were observed in both colon cancer cells after treatment with sodium taurolithocholate. Different expression changes were detected of hsa-miR-129-5p, hsa-miR-30c-5p, hsa-miR-224-5p, hsa-miR-30b-5p, hsa-miR-522-3p, and hsa-miR-1246. Finally, hsa-miR-1246 and hsa-miR-522-3p could play a critical role in tumor development via bile acid-related genes in colon cancer. Conclusion: These findings reflected that CHRM3-dependent oncogenetic pathways might be in charge of colon cancer. We suggest that the microRNA expression profile of each individual colon cancer tissue is a unique digital signature. Cite this article as: Aktan Ç, Tekin F, Oruç N, Özütemiz Ö. CHRM3-associated miRNAs may play a role in bile acid-induced proliferation of H508 colon cancer cells. Turk J Gastroenterol. 2023;34(3):298-307.